Variation in on-scene time of emergency medical services and the extent of the difference of on-scene time between genders: a retrospective population-based registry study in Riyadh Province, Saudi Arabia. Issue 3 (16th March 2022) - Moafa, Hassan N; van Kuijk, Sander MJ; Moukhyer, Mohammed E; Alqahtani, Dhafer M; Haak, Harm R
Abstract : Objectives: To identify the intergender variation of on-scene time (OST) for highly urgent emergency cases conveyed by emergency medical services (EMS) in Saudi Arabia and to assess other predictors of OST and hypothesise for possible factors delaying OST. Design: A retrospective population-based registry study. Setting: Riyadh Province is the largest province in terms of population and the second in terms of geographical area. Participants: All highly urgent transported patients from the scene to emergency departments, be they medical emergencies or trauma emergencies during 2018. Outcome measure: OST difference between men and women transported by EMS. Results: In total, 21 878 patients were included for analysis: 33.9% women and 66.1% men. The median OST for women was 22 min (IQR 15–30) and 18 min (IQR 11–26) for men (p<0.001); for medical cases, median OST was 23 min (IQR 16–31) for women compared with 20 min (IQR 13 – 29) for men (p<0.001); for trauma cases, the median OST of both sexes was equal. We found the following additional predictors of OST: factors of emergency type, sex, age category, geographical areas, type of ambulance vehicle and hospital type were all significantly associated with OST in the crude or adjusted analyses. Factors of emergency type, sex, age category, geographical areas, type of ambulance vehicle and hospital type were also significantly associated with the odds of OST of more than 15 min in the crude and adjusted regression analyses. Conclusions: The median OST was longer than 15 min for more than half of transported cases. For medical cases, women had a longer median OST than men. Additional predictors associated with prolonged OST were the patient's age, area (ie, urban vs rural), type of ambulance vehicle and season. These findings are hypothesis generating and require further studies.